Microstructure and properties analysis of the brazing alloy prepared from recycled E-waste - Yang, Jiao; Bao, Li; Long, Weimin; Zhong, Sujuan; Qin, Jian; Qiao, Ruilin (Frontiers in Chemistry, 2022)
In order to realize the efficient and comprehensive utilization of e-waste resources and short process preparation of alloy brazing materials, this study analyzed the Microstructure and properties of e-waste recycled brazing alloys using many analysis methods such as inductively coupled plasma emission spectrometer, differential scanning calorimeter, scanning electron microscope, metalloscope, X-ray diffractometer, micro-hardness tester. Experimental results showed that the circuit board recycling alloy mainly consisted of α-Fe dendrites, (Cu, Sn) phases, Sn-rich phases and Cu matrix; the alloy which obtained by pure metals is composed of (Cu, Sn) phase, Sn-rich phase and Cu matrix. There were significant differences in the phase structure of both. Compared with the alloy obtained by pure metal smelting, the melting temperature range of alloy obtained by melting the circuit board is between 985.3 and1053.0℃, which was expanded. The melting temperature becomes higher, and the shear strength is reduced. The shear strengths of two brazed joints with Multi-component brazing filler metals are 182.21 MPa and 277.02 MPa, respectively. The overall difference in hardness between the two is not important. In addition, there are a large number of precipitated phases in alloy obtained by melting the circuit board, and the main strengthening mechanism is precipitation strengthening, while the main strengthening mechanism of obtained by pure metals is solid-solution strengthening.